PELATIHAN DAN PENDAMPINGAN KADER KESEHATAN DALAM KESIAPAN GIZI MENYUSUI PADA IBU HAMIL TRIMESTER III DI KELURAHAN CIPINANG BESAR UTARA, JAKARTA TIMUR : PELATIHAN DAN PENDAMPINGAN KADER KESEHATAN DALAM KESIAPAN GIZI MENYUSUI PADA IBU HAMIL TRIMESTER III DI KELURAHAN CIPINANG BESAR UTARA, JAKARTA TIMUR (Jurnal Mitra Masyarakat (JMM), 2022)
Preparation for breastfeeding during pregnancy is important, because with good preparation, mothers are better prepared to breastfeed their babies. The preparation includes knowledge and psychological support to preparementally, and health services to prepare the mother's physical condition. Preparation be good, mothers will be more confident and ready to give exclusive breastfeeding to their babies. The mother's physical readiness can beseen from the condition of the breasts, especially the nipples, and the mother's nutrition. Based on Susenas data for 2019-2021, the national coverage of exclusive breastfeeding for infants 0-6 months, in Indonesia is still below 50 percent, meaning that more than half of Indonesian children do not get their right to exclusive breastfeeding from pregnant mother’s. Posyandu cadres have a major role in efforts to improve maternal and child health. The results showed that 63.8% of cadres strongly agreed that they played a role in the success of breastfeeding mothers. In addition, 66% of cadres need face-to-face discussion groups with health workers about breastfeeding. In carrying out their role, there are also obstacles faced by health cadres in helping breastfeeding mothers, namely feeling a failure in communicating and convincing mothers to breastfeed their babies (21.3%), not having adequate knowledge when breastfeeding mothers complain of little breast milk, small nipples, and babies do not want to breastfeed (17%). This Community Service was carried out in February 2022. The aim of increasing the knowledge and skills of posyandu cadres in providing health education to the target group for special nutrition interventions: priority targets trimester 3 pregnant women in the Cipinang Besar Utara, East Jakarta